La llengua catalana - Jané, Albert (Quaderns de cultura, 1966)
The text is in Catalan, which is a Romance language, the national language of Andorra, and a co-official language in the Spanish autonomous communities of The Balearic Islands, Catalonia and Valencia, and in the city of L'Alguer on the Italian island of Sardinia.